2015
DOI: 10.1177/0883073815592226
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the Child Neurology Program Coordinator Association: Workforce Issues and Readiness for the Next Accreditation System

Abstract: In preparation for the implementation of the Next Accreditation System in Child Neurology, the authors organized the first meeting of child neurology program coordinators in October 2014. A workforce and program-readiness survey was conducted initially. Coordinator job titles varied widely. Most respondents (65%) managed 1 or more fellowships plus child neurology residency. Most had worked in graduate medical education less than 5 years (53%), with no career path (88%), supervised by someone without graduate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 7 publications
3
11
0
Order By: Relevance
“…Few studies have evaluated the role of training for a PC. Feist and colleagues 6 found that most childneurology PCs had limited experience (, 5 years) and were supervised by someone without GME experience. These results are important as Nickel and colleagues 5 found that most PCs perform tasks and take on responsibilities beyond what is listed in their job description.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have evaluated the role of training for a PC. Feist and colleagues 6 found that most childneurology PCs had limited experience (, 5 years) and were supervised by someone without GME experience. These results are important as Nickel and colleagues 5 found that most PCs perform tasks and take on responsibilities beyond what is listed in their job description.…”
Section: Discussionmentioning
confidence: 99%
“…3 There are only a few studies that outline the optimal form and content for the successful training of specialty-specific PCs. [4][5][6][7][8][9] Current practice for the onboarding of PCs involves an orientation about their duties and expectations from the GME office at their specific institutions (GME training). Occasionally, new PCs may receive direction and assistance from their peers in a one-on-one setting prior to assuming the responsibilities of the position (peer training).…”
Section: Introductionmentioning
confidence: 99%
“…Neurosurgery residency program coordinators play an important role in the organization and function of residency and fellowship programs. In addition to managing the daily operation of these programs, coordinators must manage Accreditation Council for Graduate Medical Education (ACGME) requirements for program accreditation in direct coordination with the program director(s), department chair, and other department staff [1-3]. First formalized in 2008, the Society of Neurosurgical Surgeons Coordinator’s Group grew out of the increasingly formalized ACGME requirements for neurosurgery departments.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are several established Graduate Medical Education (GME) and ACGME requirements and guidelines for program coordinators, but except for the requirement that there must be a program coordinator with at least 50% of his or her time dedicated to the residency program, these are not consistent across specialties [1,3,8]. The only specified ACGME requirement for neurosurgical program coordinators states, “There should be a full-time designated program coordinator with financial support from the sponsoring institution” [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation